Connaissances médicales actuelles, cotation des enthésopathies : nouvelle méthode - Sébastien Villotte (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Over the last twenty years, many studies have used enthesopathies as an indicator of the behaviour of past populations. However, in these works, the distinction between healthy and pathological aspects has been arbitrary. Moreover the lack of standardised observation methods exacerbates this problem and limits the comparison between different studies. The aim of this study is to propose a new method of studying enthesopathies based on present medical data. It is possible to distinguish two types of entheses according to the nature of the tissue of insertion: fibrous or fibrocartilaginous. The variations between normal and pathological aspects based on this distinction enable the proposition of four generic scoring systems. These systems were applied to 18 sites of appendicular insertions and spinal column insertions of yellow ligaments. Under each system, three scoring stages are defined representing different stages of the remodelling process. The first three groups include fibrocartilaginous insertions. We used anatomical and anatomopathological descriptions to define the stages. Such descriptions are rare for the fourth group which concerns fibrous insertions. With this method, intra- and inter-observer errors are less than 10%. Application of this scoring method on archaeological skeletons of known age, sex and activity would allow us to discuss the respective relevance of the use of fibrous and fibrocartilaginous entheses for the interpretation of behaviour and activities of past human populations.